Apolipoprotein E4 heterologous expression, purification under non-denaturing conditions, and effects on neuronal clonal cell lines - Serrano, Ezequiel (2023)
Fil: Serrano, Ezequiel. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Laboratorio de Neurobiología Molecular; Argentina